SlATG8f modulates tomato thermotolerance and fruit quality, correlating with changes in autophagy and heat shock-related genes - Qunmei Cheng; Wen Xu; Cen Wen; Zhuo He; Liu Song (PLoS ONE, 2026)
Plant responses to high-temperature stress involve intricate changes in physiology bio-chemistry, and gene expression. Autophagy, a conserved intracellular degradation system, aids in eliminating damaged cellular components and is crucial for plant growth, development, and stress adaptation. Despite the known functions of many autophagy-related genes under high temperatures, the specific role of SlATG8f in tomatoes remains unclear. In this study, SlATG8f OE tomato lines were created using the pBWA(V)HS vector. Through quantitative reverse transcription polymerase chain reaction (qRT-PCR), we assessed physiological parameters, expression levels of ATG8 family members, and heat shock protein-related genes in fruits of wild-type (WT)and SlATG8f OE plants at four developmental stages under high-temperature stress. Our findings demonstrate that SlATG8f OE enhances the expression of autophagy-related and heat shock protein genes, accelerates fruit ripening, and enhances fruit quality under high-temperature conditions. These results highlight the regulatory function of SlATG8f in preserving tomato fruit quality during heat stress and offer a basis for enhancing tomato varieties.